Income Analysis and Business Feasibility of Permanent Rice Mills in Laubaleng District, Karo Regency - Ipandi; Ekowati, Titik; Roessali, Wiludjeng (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2023)
This research was conducted in three permanent rice mills located in Laubaleng District, Karo Regency, they are Dison Tani rice mill, Karunia rice mill and Akung rice mill. This research aimed to analyze the revenue and the feasibility of the rice milling in Laubaleng District. The revenue of rice mills business was analyzed by cost and income analysis formula. Analytical tools that used to analyze business feasibility were Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), Payback Period (PP) and Return on Investment (ROI). Result showed that the average income was Rp 360.246.698/year and the profitability was 6,13%. The NPV value of the permanent rice milling business in Laubaleng District is Rp 179.141.461, IRR values is 19,51%, PI value is 1,19, PP is 3 years 3 month and ROI is 35,65%. Based on that results, permanent rice mills in Laubaleng District are profitable and feasible to develop.